Cytopathology An Introduction - Sheaff, Michael T.; Singh, Naveena (Springer London : Imprint: Springer, 2013)
Cytopathology: An Introduction is a succinct book which guides the trainee through the hurdles of early cytology practice and can also be used throughout the career as an aide memoire by the more experienced. With numerous illustrations to enthuse the reader and make cytological practice a more enjoyable and educational experience, Cytopathology: An Introduction also highlights points of diagnostic difficulty, particularly with regard to the differentiation of neoplastic from non-neoplastic disease.  Each chapter of Cytopathology: An Introduction starts by detailing the main methods available appropriate to the clinical situation, followed by descriptions of the relevant cytological appearances and diagnostic pitfalls. Topics covered include the brain and cerebrospinal fluid; pulmonary cytology; serous fluids; thyroid gland; lymph nodes; salivary glands; gastrointestinal and hepatopancreaticobiliary tracts; urinary tract and retroperitoneal cytology; female genital tract; breast; soft tissue, bones and joints; and skin.  Cytopathology: An Introduction will be an invaluable reference guide to histo- and cytopathology trainees, as well as those preparing for post-graduate examinations and consultants who want a refresher. A quick reference, concise but precise, Cytopathology: An Introduction provides practical and helpful information on the salient cytological features of any condition that may present in routine cytopathology.